The Antimicrobial Extract Derived from Pseudomonas sp. HP-1 for Inhibition of Aspergillus flavus Growth and Prolongation of Maize Seed Storage - Marhaba Kader; Liping Xu; Longteng Fang; Reziyamu Wufuer; Minwei Zhang; Nan Wei; Dong Wang; Zhiwei Zhang (Foods)
Maize, one of the most widely cultivated crops globally, is highly susceptible to mycotoxin contamination. In this study, an endophytic strain Pseudomonas sp. HP-1, isolated from Peganum harmala L., demonstrated significant biocontrol potential. The culture extract of Pseudomonas sp. HP-1 (PHE) exhibited strong antifungal activity, with inhibition zones of 40.07 ± 0.21 mm against Penicillium italicum, 29.71 ± 0.25 mm against Aspergillus niger, and 23.10 ± 0.44 mm against A. flavus, along with notable antibacterial activity against Staphylococcus aureus (22.43 ± 0.55 mm). At a concentration of 16 mg/mL, PHE almost completely inhibited the mycelial growth of A. flavus. The antifungal mechanism of PHE was investigated through scanning electron microscopy (SEM) and propidium iodide (PI) staining analysis, which demonstrated that antifungal activity is primarily through the disruption of cellular membrane integrity. Furthermore, PHE significantly reduced the incidence of A. flavus contamination in agroecological maize seeds during storage, and treated PHE showed superior antifungal efficacy compared to non-treated PHE, highlighting its potential as an effective antifungal agent for seed protection. Through one- and two-dimensional NMR and MS analyses, the primary active compound of PHE was identified as 1-phenazinecarboxylic acid. These findings indicate that PHE can be utilized as a sustainable antifungal agent for protecting maize seeds against mycotoxin-producing fungi.